Pengembangan Augmented Reality Sebagai Media Simulasi Pada Mata Pelajaran IPAS Tata Surya di SMK Negeri 4 Palangkaraya - Noviyanti, Naydia; Permadi, Ade Salahudin; Fitriyanto, Muhammad Noor (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2025)
The rapid development of information and communication technology in the digital era has had a significant impact on various sectors, including education. However, the teaching of Natural and Social Sciences (IPAS) still often relies on textbooks and underutilizes interactive media such as Augmented Reality (AR). This reliance makes abstract topics, like the Solar System, difficult for students to understand. The lack of media variety and teaching methods also contributes to students' low interest and comprehension of the material. Therefore, this research aims to develop AR-based simulation media as a more engaging, interactive, and effective alternative to help students grasp the concepts of the Solar System. This study employs a Research and Development (R&D) method that consists of five stages: analysis, design, development, implementation, and evaluation. The development of the simulation media utilizes software such as Unity, Blender, and Vuforia technology to support Augmented Reality features. The developed product was validated by educational media experts and content specialists to ensure its feasibility in terms of both content and technical aspects. Subsequently, a limited trial was conducted with students from class X-GP to assess the practicality and appeal of the developed media. The results of the study indicate that the AR simulation media on the topic of the Solar System is highly suitable for use in the learning process. Validation from experts shows that this media is categorized as "very feasible" in terms of content, visualization, and technical aspects. The limited trial in class X-GP at SMK Negeri 4 Palangka Raya demonstrated a significant improvement in students' understanding, with N-Gain scores falling within the "medium" to "high" categories. Additionally, students provided very positive feedback regarding this media, finding it engaging, interactive, easy to operate, and effective in helping them understand abstract material like the Solar System in a more concrete and enjoyable way compared to conventional methods that rely on textbooks. Thus, this AR-based simulation media is recommended as an alternative teaching resource to enhance the quality of the learning process for the Solar System material in the IPAS subject.